Student Participation and Achievement through Student Facilitator and Explaining Model: Partisipasi dan Prestasi Siswa melalui Model Student Facilitator and Explaining - Dea Galuh Firdianti; Subhanadri; Refril Dani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education in elementary schools requires strategies that encourage active learning and meaningful understanding. Specific Background: In SDN 109/II Manggis, only 29% of fifth-grade students met the minimum criteria in Natural and Social Sciences (IPAS), indicating low mastery and passive learning. Knowledge Gap: While the Student Facilitator and Explaining (SFAE) model has been applied in other subjects, its role in IPAS learning remains underexplored. Aims: This study aimed to improve the learning process and outcomes of IPAS by applying the SFAE model. Results: Conducted through Classroom Action Research (two cycles, 23 students), the study showed consistent improvements. Teacher performance rose from 73.68% to 89.47%, student activity from 59% to 79.33%, and classical mastery from 55.56% to 81.49%. Students became more active in discussions and peer explanations, leading to stronger understanding and retention. Novelty: This research applies SFAE specifically in IPAS, a newly integrated subject in the independent curriculum, highlighting its potential in contextual science-social learning. Implications: Findings suggest that SFAE fosters collaborative learning, student participation, and academic achievement, making it suitable for wider application in similar classroom contexts. Highlight Active learning with peer explanation improved student mastery in IPAS. Teacher and student performance increased across research cycles. SFAE fostered collaboration and meaningful engagement in learning. KeywordStudent Facilitator And Explaining, Elementary Education, Science Learning, Classroom Action Research, Student Participation